The epidemiology of surfing injuries in a major Australian Centre – A ten year clinical audit. Issue 6 (June 2022) - Quinn, Jonathan; Salmon, Luke; Ngo, Donald; Taylor, Fraser; Platt, Simon
Highlights: Over half (56.4%) of surfing injuries sustained were orthopaedic in nature. Lacerations, ligament injury and fractures were the 3 most common injury types. Head and cervical spine was the most common injury location followed by lower limb and upper limb. Our findings will aid musculoskeletal screening in key injury-prone areas upon presentation to the emergency department. Strategic use of orthopaedic staff and resources are required at coastal or tertiary hospitals to address surfing injuries. Abstract: Introduction: Australia is one of the largest surfing nations with over 10% of the population participating; yet there is a paucity of literature analysing the injuries from surfing participation, particularly injuries requiring orthopaedic care. This study retrospectively analyses surfing injuries presenting to a tertiary hospital Emergency Department over a ten-year period with aims of quantifying surfing injuries and investigating injury characteristics requiring orthopaedic input. Methods: A retrospective clinical audit of presentations to Gold Coast Public Hospital Emergency Departments over a ten-year period was conducted using electronic hospital databases. Broad search teams were used to identify presentations, followed by exclusion based on relevance. Subsequent analysis of data was performed to investigate patient demographics and injury characteristics. Results: A total of 2680 surfing related injury presentations were analysed. The median age was 30 years (range 2–77), with 455 females (17%) and 2225 males (83%). Lacerations were the most common injury type (37.9%), followed by ligament injury (21.3%), fractures (12.2%), and contusions (11.4%). The most common areas for lacerations were head/face (59.2%), lower limb (30%), and upper limb (26.5%). Dislocation rate was 4.9%, with shoulder dislocation (76.5%), and patella dislocation (12.1%) being the most common types. 1512 presentations (56.4%) required orthopaedic management. 93.5% did not require admission and were discharged. Conclusion: Over half (56.4%) of surfing injuries were orthopaedic in nature; requiring orthopaedic advice or management. Lacerations, ligament injury, fractures and dislocations were the most commonly managed injuries. This emphasises the importance of understanding the prevalence and characteristics of surfing injuries for an orthopaedic service.